Implementación de solución BI para la gestión de datos en una institución educativa en el periodo 2021-2023 - Riofrío Ramón, Richard Eduardo (2024)
The degree work: “Implementation of a BI solution for data management in an educational institution in the period 2021-2023” aims to improve the management of information in the educational institution through efficient development in decision making, with the use of business intelligence strategies. To carry out the following degree work, some research methodologies were used, among which active observation and case study stand out. As well as techniques and instruments such as interviews, bibliographic review, surveys to identify the problem, creation of the schedule and budget, were also used. By applying interviews to the personnel in charge of managing the processes of the educational institution, especially administrative personnel, it is possible to analyze the state of the institution as a company. The scope focuses on activities directly related to the implementation of the BI solution and does not include structural or policy changes not linked to data management. It is determined that the institution manages operating data that makes up the crucial information for the company's decision making, which requires adequate monitoring to develop an action plan and improvement strategies. The solution provided by intelligence focuses on the extraction of detailed and specific information in real time, aligned with the performance of the institution in different aspects. For the development of this solution, the business intelligence tool based on the Pentaho suite is used, where some of the applications that fulfill functions in different areas are embedded. The argument of this degree work is based on the creation of a database, the extraction, transformation and loading of the data to later be presented and processed for decision making within the company and improve the service in academic offer. and strengthening the quality of education. Keywords: Business intelligence, Company, data extraction, transformation